Uterine fluid proteome changes during diapause and resumption of embryo development in roe deer (Capreolus capreolus). Issue 1 (July 2019) - van der Weijden, V A; Bick, J T; Bauersachs, S; Arnold, G J; Fröhlich, T; Drews, B; Ulbrich, S E
Abstract : The uterine microenvironment during pre-implantation presents a pro-survival milieu and is essential for embryo elongation in ruminants. The European roe deer ( Careolus capreolus ) pre-implantation embryo development is characterised by a 4-month period of reduced development, embryonic diapause, after which the embryo rapidly elongates and implants. We investigated the uterine fluid proteome by label-free liquid chromatography tandem mass spectrometry at four defined stages covering the phase of reduced developmental pace (early diapause, mid-diapause and late diapause) and embryo elongation. We hypothesised that embryo development during diapause is halted by the lack of signals that support progression past the blastocyst stage. Three clusters of differentially abundant proteins were identified by a self-organising tree algorithm: (1) gradual reduction over development; (2) stable abundance during diapause, followed by a sharp rise at elongation; and (3) gradual increase over development. Proteins in the different clusters were subjected to gene ontology analysis. 'Cellular detoxification' in cluster 1 was represented by alcohol dehydrogenase, glutathione S-transferase and peroxiredoxin-2. ATP-citrate synthase, nucleolin, lamin A/C, and purine phosphorylase as cell proliferation regulators were found in cluster 2 and 'cortical cytoskeleton', 'regulation of substrate adhesion-dependent cell spreading' and 'melanosome' were present in cluster 3. Cell cycle promoters were higher abundant at elongation than during diapause, and polyamines presence indicates their role in diapause regulation. This study provides a comprehensive overview of proteins in the roe deer uterine fluid during diapause and forms a basis for studies aiming at understanding the impact of the lack of cell cycle promoters during diapause.